Efficacy and safety of Chinese herbal medicine in post-stroke epilepsy: a systematic review and meta-analysis - Sun, Tianye; Wang, Kaiyue; Li, Lili; Yan, Mingyuan; Wu, Jing; Liu, Jinmin (Frontiers in Pharmacology, 2023)
Background and objective: This study aimed to evaluate the efficacy and tolerability of Chinese herbal medicine (CHM) adjunctive therapy in the treatment of Poststroke epilepsy (PSE). Methods: A systematic search of eight databases was conducted to identify PSE-related randomized clinical trials from the inception of each database through October 2023. The methodological quality assessment was conducted by RoB 2.0, meta-analysis was conducted by RevMan 5.3 and Stata 15.1. Results: Twenty-three RCTs involving 1,901 PSE patients were identified. We found that orally administered CHM plus conventional Western medicine (CWM) was superior to CWM monotherapy in increasing the 75% responder rate (RR 1.46, 95% CI: 1.31 to 1.62, p < 0.00001), decreasing the seizure duration (MD -1.01, 95% CI: -1.30 to -0.72, p < 0.00001), improving total responder rate (RR 1.29, 95% CI: 1.20 to 1.37, p < 0.00001), reducing epileptiform discharges(MD -2.02.46, 95% CI: -2.64 to -1.40, p < 0.00001), and decreasing the number of leads involved in epileptiform discharge (MD -3.92, 95% CI: -5.15 to -2.68, p < 0.00001). Furthermore, intravenously administered CHM plus CWM was superior regarding 75% responder rate (RR 1.39, 95% CI: 1.24 to 1.56, p < 0.00001), total responder rate (RR 1.29, 95% CI: 1.20 to 1.39, p < 0.00001), EDs (MD -3.92, 95% CI: -5.15 to -2.68, p < 0.00001), and the number of leads involved in epileptiform discharge (MD -1.82, 95% CI: -2.62 to -1.02, p < 0.00001). However, regarding the 50%-75% responder rate, there was no statistically significant difference between the two groups for either oral (RR 1.00, 95% CI: 0.77 to 1.29, p = 0.98) or injectable CHM (RR 0.95, 95% CI: 0.67 to 1.33, p = 0.75). Both orally administered CHM plus CWM (RR 0.56, 95% CI: 0.35 to 0.90, p = 0.02) and intravenously administered CHM plus CWM (RR 0.64, 95% CI: 0.45 to 0.90, p = 0.010) caused fewer AEs than CWM. Conclusions: CHM adjuvant therapy may be an effective and safe therapy for PSE. However, due to the poor quality of clinical data, more well-designed RCTs are needed to confirm these findings.